The status of accounting information systems (AIS) adoption in the hotel industry - Ainon Ramli (http://fkp.umk.edu.my/journal/download/4-v3.pdf, 2015)
The work systems of organizations nowadays depend on IT. Hospitality industry is one of the industries affected by the IT revolution. Studies on the use of Accounting Information Systems (AIS) in the hotel industry, especially in developing countries, are limited. Thus, this research attempts to fill the knowledge gap by exploring the adoption of AIS in the Malaysian context. The research adopts a survey approach where the data were collected through a postal questionnaire from senior accounting managers in three, four, and five star rated hotels. A total of 101 completed and usable questionnaires were gathered from a total of 367 mailed questionnaires, giving a response rate of 27.52%. The findings confirm the wide use of computerized accounting systems in the hotels, although, the extent of the AIS use is relatively unsophisticated with the focus on basic accounting modules and fundamental accounting-based applications.